Factors Affecting Millennials Purchase Intention and Sustainable Consumption of Organic Food - Ni Made Dewi Ayu Murti; Ardhianiswari Diah Ekawati (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2022)
Organic food refers to the products produced in conventional way, without hazardous materials. Millennials are the generation most attractive to organic food market. This study aims to analyze whether factors such as environmental knowledge, environmental awareness, health awareness and social awareness affecting purchase intention and sustainable consumption of the millennials towards organic food. A questionnaire used to evaluate the relationships between the six constructs. The findings showed that 340 respondents have met requirements for analysis. The method used was Structural Equation Model (SEM). The research findings find out the main factors that influence purchase intention and sustainable consumption of the millennial generation towards organic food. This research is expected to help non-governmental organizations increase purchase intention and investigate factors that influence the sustainable consumption of organic food in the millennial generation. This research has implications for the organic food industry, especially organic food producers, namely by applying the packaging sustainability method to reduce waste in the environment.